The Main Event : Boxing in Nevada from the Mining Camps to the Las Vegas Strip - Davies, Richard O., 1937- (Book collections on Project MUSE., 2014)
"Nevada has a rich tradition of boxing that is deeply embedded in the culture of the state. Beginning in the late-19th century, Nevada played a key role in the history of the sport when it hosted the Fitzsimmons-Corbett contest in 1897, and then later the Johnson-Jeffries match in 1910. In the second half of the 20th century, Las Vegas became the center of American boxing. The state has also been home to important boxing personalities like Tex Rickard, Mills Lane, and Mike Tyson. The Main Event is the first comprehensive cultural history of boxing in the Silver State, tracing the sport from its origins in 19th century mining camps to the mixed martial arts of contemporary Las Vegas. Davies utilizes both secondary and primary sources to analyze boxing within Nevada's tourist economy, morally libertarian values, and other unique aspects of the state's history and culture. He pays particular attention to how boxing in the Silver State has intersected with issues of race, class, and gender. Written in an engaging style that shifts easily between analysis and narrative, The Main Event will appeal to both scholars and the general reading public"--